Chapter 5 FinTechs, BigTechs and structural changes in capital markets - Harasim, Janina (Taylor & Francis, 2022)
This chapter aims at exploring some theoretical issues associated with the impact of technology companies on the market structure in the financial industry with the special focus on capital markets. Based on the industrial organization theory, as well as on an extensive literature review, research to date, and industry reports, the attempt was made to identify main structural changes resulting from FinTech's activity in this market segment. It was found that, in contrast to the banking sector, BigTechs are not interested in entering into capital markets. This can be explained by complexity of investment services and weak synergies between them and non-financial services offered by technology giants. As a result, digitalization in capital markets is driven rather from inside and supported by FinTechs. In the stock market, the development of high-frequency trading resulted in the increasing centralization of trade that neither facilitated market access nor eliminated the market asymmetry. Nonetheless, FinTech solutions allowed reductions in transaction costs and increase in short-term market efficiency. In the asset management and mutual funds industry digital platforms, developed mostly by incumbents, by lowering transaction costs and reducing communication frictions made investing easier and cheaper for individuals, however their decisions became more speculative.